Guidelines on how to use application software: Inkodo / Noor Azizah Mazeni... [et al.] - Mazeni, Noor Azizah; Idris, Nur Azimah; Samsudin, Norshuhada; Syed Abdullah, Sharifah Sarimah (Unit Penerbitan JSKM, 2020)
The government of Malaysia announced the Movement Control Order (MCO) when Malaysia was hit with high number of COVID-19 cases which has forced the closure of schools and higher education institutions temporarily. This situation challenged the education system and forced educators to shift their teaching mode from face to face to an open distance learning method. In order to support and enhance virtual learning, educators need to adapt to various online teaching methods including preparing compact and dynamic notes for the students. This article focused on writing application softwares (apps) which is Inkodo. It can be conveniently downloaded through Microsoft Store and plus, it is a free app. The objective of this article is to share a helpful guideline to new users. This includes on how to create a book and also descriptions on most of the icons in the page editor. Inkodo is a user-friendly apps where users can annotate on empty sheets, documents as well as images. Ink it with the help of stylus and writing pads and users will surely be satisfied with all the features in this apps.